Preparation method of environment-friendly waterborne polyurethane modified butyronitrile latex and application of environment-friendly waterborne polyurethane modified butyronitrile latex in labor protection gloves

By modifying the water-based polyurethane of nitrile latex, the problems of insufficient durability and poor breathability of labor protection glove materials are solved, achieving higher wear resistance and durability, while improving the feel and wear comfort.

CN120192600APending Publication Date: 2025-06-24HANGZHOU TRANSFAR FINE CHEM CO LTD +2
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510305419.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-14
Publication Date
2025-06-24

AI Technical Summary

Technical Problem

The existing labor-protecting glove material nitrile latex has problems such as insufficient durability, poor breathability, lack of softness and skin-friendliness, and is prone to peeling and wear during use.

Method used

By using water-based polyurethane to modify the nitrile latex, it has the characteristics of acid-coagulant salt non-coagulant, improves its penetration performance and yarn binding ability, enhances the wear resistance and durability of the gloves, and improves the feel of the hand.

Benefits of technology

It significantly improves the wear resistance and durability of labor protection gloves, allowing them to maintain good performance in various working environments, and improves the feel and provides better wear comfort.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120192600A_ABST
    Figure CN120192600A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of environment-friendly waterborne polyurethane modified butyronitrile latex and application of the environment-friendly waterborne polyurethane modified butyronitrile latex in labor protection gloves. The leather working gloves prepared from the waterborne polyurethane modified butyronitrile latex not only have excellent wear resistance of the butyronitrile latex, but also overcome the limitation of the traditional butyronitrile leather working gloves, and the durability and softness of the gloves are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of labor protection glove preparation, and particularly relates to a preparation method of an environment-friendly waterborne polyurethane-modified nitrile latex and its application in labor protection gloves. Background Art

[0002] With the continuous enhancement of personal protective safety awareness, labor protection gloves have become an indispensable and basic protection means in people's production activities. Due to its low cost and excellent physical properties, nitrile latex has long been widely used as the main material for producing labor protection gloves. However, this material system always has problems such as insufficient durability, poor breathability, and lack of softness and skin-friendliness.

[0003] The poor durability is mainly due to the following two aspects. In the labor protection glove preparation process, the coagulants selected are mainly calcium salts or methanol solutions of acetic acid. Nitrile shows good coagulation effects in both of these solutions, which leads to that no matter which coagulant is selected, after the glove core is dipped in the coagulant and then dipped in the glove glue, the colloid instantly demulsifies and solidifies on the surface of the glove core and will not further penetrate into the glove core. When the colloid only floats on the surface of the glove core, its binding effect on the yarn will also be very limited. In this way, labor protection gloves are very easy to peel off from the glove core during repeated use and scrubbing, which not only greatly reduces the durability of labor protection gloves but also increases the use cost.

[0004] In addition, although the high-density cross-linked structure of nitrile rubber can provide basic protection, the material is inherently rigid, resulting in the lack of flexibility of the gloves. During wearing, local stress concentration is easily generated due to repeated bending, which not only accelerates surface wear (especially in high-friction areas such as knuckles and palms) but also compresses the hand muscles, causing fatigue and even skin indentations. After long-term operation, microcracks are easily generated on the inner wall of the gloves due to friction, further reducing the durability.

[0005] The molecular structure of nitrile latex is relatively compact, which will hinder the volatilization of sweat and form a closed humid and hot environment. The retention of sweat not only causes sticky discomfort but also softens the stratum corneum of the skin, exacerbating the frictional damage between the inner wall of the gloves and the skin. In addition, the humid and hot environment is prone to breeding bacteria, resulting in hand odor and even allergic reactions. Although briefly improving the wearing experience can be achieved by simply reducing the material hardness or adding a foaming agent, the protective performance will be sacrificed - after the material is loosened, it is easily pierced by sharp objects and the wear-resistant life is greatly shortened. And the composite process of an outer coating often shows delamination and peeling after repeated bending due to insufficient interfacial bonding force, instead forming a new wear source.

[0006] In addition, anionic external emulsifiers are used as hydrophilic stabilizers for nitrile latex. This stabilizer covers the surface of nitrile rubber particles, thereby forming a stable emulsion structure and existing in water. However, when this structure encounters salt solutions and acid solutions, the hydrophilic layer will be damaged, resulting in easy flocculation and precipitation from water, forming micelles or films. However, at the current stage, during the production process of labor protection gloves, a calcium salt solution must be used to pretreat the glove cores to prevent glue penetration; and an acidic solution is used for post-treatment to accelerate the shaping process of labor protection gloves and give them a more beautiful appearance. The pretreatment process with calcium salt solution results in insufficient firm bonding between the nitrile latex and the glove core fibers. The nitrile rubber film adheres to the surface of the yarn, and the tying effect of the yarn is poor. As a result, the labor protection gloves feel rigid, have unsatisfactory abrasion resistance, and poor durability. Summary of the Invention

[0007] In view of the above problems, the present invention provides a preparation method of an environmentally friendly waterborne polyurethane-modified nitrile latex and its application in labor protection gloves. By using special waterborne polyurethane to modify the nitrile latex, it has the characteristics of non-coagulation in acid and coagulation in salt. After mixing with nitrile, the penetration performance into the glove core is significantly improved compared to the pure nitrile system, and the yarn-tying ability of the nitrile latex is significantly enhanced. This improvement not only enhances the abrasion resistance and durability of labor protection gloves, enabling them to maintain good performance in various working environments, but also effectively improves the hand feeling of the nitrile latex through the flexibility and fleshiness provided by polyurethane.

[0008] One of the technical solutions of the present invention is to provide a preparation method of an environmentally friendly waterborne polyurethane-modified nitrile latex, which has the following steps: (1) Prepare vulcanized nitrile; (2) Prepare polyurethane; the proportion of polyol in the polyurethane structure is 60wt%-85wt%; the functionality of the polyol is 3-6, the PO / EO ratio is 20%-50%, and the number average molecular weight is 2000-6000; (3) Mix vulcanized nitrile and waterborne polyurethane resin according to a mass ratio of (80-95):(5-20) to obtain a mixture of vulcanized nitrile and waterborne polyurethane resin. Add 75-87 parts by weight of the mixture of vulcanized nitrile and waterborne polyurethane resin, 4-10 parts by weight of deionized water, 5-10 parts by weight of thickener, 1-2 parts by weight of white paste, and 0.5-1 part by weight of black paste, and then mechanically foam to 1.2 times the original volume and stabilize the foam for 5-10 minutes; finally, add thickener to make the above mixture reach a construction solid content of 38-42wt% and a viscosity of 1500-1800cp to obtain the environmentally friendly waterborne polyurethane-modified nitrile latex.

[0009] Further, the method for preparing vulcanized nitrile in Step 1 is as follows: adjust the pH value of the nitrile latex to 9 - 10 with a 5wt% potassium hydroxide solution, add 50wt% zinc oxide slurry, 50wt% sulfur powder slurry, and 50wt% accelerator slurry while stirring, and keep stirring for 24 - 48 hours after mixing evenly to obtain vulcanized nitrile.

[0010] The mass ratio of the zinc oxide slurry, sulfur powder slurry, and accelerator slurry is (30:50):(10 - 15):(8 - 15).

[0011] Further, the method for preparing polyurethane in Step 2 is as follows: (1) Under the protection of nitrogen, dehydrate 40 - 80 parts by weight of polyol at 100 - 120°C for 2 - 5 h. When the water content is below 500 ppm, add 8 - 20 parts by weight of isocyanate, 2 - 6 parts by weight of hydrophilic chain extender, and 0.5 - 3 parts by weight of small molecule alcohol chain extender, stir evenly, then add 0.003 - 0.02 parts by weight of bismuth isooctanoate and 1 part by weight of acetone, and react at 70 - 95°C for 1 - 3 h to obtain a polyurethane prepolymer; the polyol is an amorphous polyether polyol with a number average molecular weight of 2000 - 6000, a functionality of 3 - 6, and a PO / EO ratio of 20 - 50%; (2) Cool the prepolymer obtained in step (1) to 50 - 55°C, add 20 - 30 parts by weight of acetone for dilution, stir evenly, and then add 0.5 - 3 parts by weight of triethylamine and stir for 1 - 15 min; (3) Emulsify with 45 - 55 parts by weight of deionized water, add 0.5 - 3 parts by weight of small molecule amine chain extender, and obtain an aqueous polyurethane emulsion after vacuum rotary evaporation to remove the solvent.

[0012] Further, the isocyanate includes one or more of toluene diisocyanate, isophorone diisocyanate, and p-phenylene diisocyanate; The hydrophilic chain extender includes one or more of dihydroxypropionic acid, sodium N-(2-aminoethyl)-2-aminoethanesulfonate, and polyoxyethylene ether; The small molecule alcohol chain extender includes one or more of neopentyl glycol, 1,4-butanediol, and 1,6-hexanediol; The small molecule amine chain extender includes one or more of diethylenetriamine, sodium N-(2-aminoethyl)-2-aminoethanesulfonate, and ethylenediamine; Further, the thickener in Step 3 is 2wt% carboxymethyl cellulose.

[0013] The second technical solution of the present invention is to provide an environmentally friendly aqueous polyurethane-modified nitrile latex prepared by the above preparation method.

[0014] The third technical solution of the present invention lies in providing the application of the above-mentioned environmentally friendly waterborne polyurethane-modified nitrile latex in labor protection gloves, and the application method is as follows: First, preheat the hand mold in an oven at 40-45 °C for 30 minutes. After taking it out, put the glove core on the hand mold. First, dip the palm downward in the coagulant, take it out and flash dry for 40-60 seconds. Then dip the palm downward in the environmentally friendly waterborne polyurethane-modified nitrile latex, take it out and shake off the latex that cannot adhere to the surface. Then dip the rubber surface in the surface treatment agent for 2-3 seconds, take it out and air dry at room temperature for 30 minutes, put it in an oven at 90 °C and bake for 40 minutes, take it out and wash it with water, and then carry out programmed temperature baking. Finally, nitrile-mixed polyurethane gloves are obtained.

[0015] Further, the coagulant is a 1.5-3 wt% calcium nitrate methanol solution; the surface treatment agent is a 5-10 wt% acetic acid methanol solution.

[0016] Further, the programmed temperature rise is baking at 90 °C for 40 minutes, baking at 105 °C for 20 minutes, and baking at 110 °C for 10 minutes.

[0017] The beneficial effects of the present invention are as follows: Through the blending modification of nitrile rubber and functional waterborne polyurethane resin, based on the anti-electrolyte gelation stability of the waterborne polyurethane resin, the permeation kinetic performance of the blended latex is significantly improved, thereby optimizing the denseness and wear resistance of the surface coating of the substrate.

[0018] The polar block molecular structure of the waterborne polyurethane resin can enhance the interfacial wettability of the fiber substrate. Through the synergistic action of hydrogen bonds and covalent bonds, the interfacial bonding strength between the colloid and the substrate is significantly improved. At the same time, the soft segment continuous phase and hard segment microphase separation structure of the waterborne polyurethane resin endow the material with low modulus flexibility and high water vapor permeability, effectively improving the touch stiffness and air permeability defects caused by the hydrophobic cross-linked network of traditional nitrile rubber. Description of the Drawings

[0019] Figure 1 It is a microscope photograph of Example 1.

[0020] Figure 2 It is a microscope photograph of Comparative Example 1. Detailed Embodiments

[0021] The following examples are used to further illustrate the present invention, and their purpose is to illustrate the present invention and should not be construed as limiting the scope of the present invention. Unless otherwise specified below, all are in parts by weight and weight percentages.

[0022] The raw materials used in the present invention, unless otherwise specified, are all conventional commercially available products; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.

[0023] The accelerator slurry described in the present invention is a commercially available product, which is ZDBC accelerator.

[0024] The embodiments of the present invention will be further described below with reference to multiple examples.

[0025] It should be clear that the described embodiments are only a part of the embodiments of the present application, rather than all of them. All other embodiments obtained by those of ordinary skill in the art based on the embodiments in the present application without creative work belong to the scope of protection of the present application.

[0026] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "the" and "said" used in the embodiments of the present application and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.

[0027] Example 1 1. Preparation of vulcanized nitrile rubber: Take 1000 g of nitrile rubber, add 30 g of 5 wt% potassium hydroxide aqueous solution to adjust the pH value to 9, and add 30 g, 10 g and 8 g of 50 wt% zinc oxide slurry, 50 wt% sulfur powder slurry and 50 wt% accelerator slurry respectively to the nitrile rubber while stirring, and continuously stir at low speed for 24 hours.

[0028] 2. Preparation of polyurethane: (1) Under the protection of nitrogen at 100 °C, dehydrate 40 parts by weight of polyol for 2 h. When the water content is below 500 ppm, add 8 parts by weight of toluene diisocyanate, 2 parts by weight of dihydroxypropionic acid, 0.5 part by weight of neopentyl glycol, stir evenly, then add 0.003 part by weight of bismuth isooctanoate and 1 part by weight of acetone, and react at 70 °C for 1 h to obtain a polyurethane prepolymer; the polyol is a non-crystalline polyether polyol with a number average molecular weight of 2000, a functionality of 3, and a PO / EO ratio of 20%; (2) Cool the prepolymer obtained in step (1) to 50 °C, add 20 parts by weight of acetone for dilution, stir evenly, and then add 0.5 part by weight of triethylamine and stir for 15 min; (3) Emulsify with 45 parts by weight of deionized water, add 0.5 part by weight of diethylenetriamine, and obtain an aqueous polyurethane emulsion after vacuum rotary evaporation to remove the solvent.

[0029] 3. Take 80 g of vulcanized nitrile rubber, mix 7 g of aqueous polyurethane resin, stir evenly, add 10 g of deionized water, and then add 10 g of 2 wt% sodium carboxymethyl cellulose aqueous solution. Add 2 g of white slurry and 1 g of black slurry, stir evenly, mechanically foam to 1.2 times, then stabilize the foam at low speed for 10 minutes, and finally adjust the solid content of the latex to 38 wt% with deionized water or 2 wt% sodium carboxymethyl cellulose aqueous solution, and the construction viscosity is 1500 cp.

[0030] 4. First, preheat the hand mold in an oven at 40°C for 30 minutes. After taking it out, put the glove core on the hand mold. First, immerse it with the palm down in a 1.5 wt% calcium nitrate methanol solution, take it out and flash dry for 50 seconds. Then, immerse it with the palm down in the prepared latex, take it out and spin the latex 20 times. Then, slowly immerse the rubber surface in a 5 wt% acetic acid methanol solution for 3 seconds, take it out and air dry at room temperature for 30 minutes. Put it in an oven at 90°C and bake for 40 minutes. After taking it out, wash it with water, and then carry out programmed temperature baking at 90°C for 40 minutes, 105°C for 20 minutes, and 110°C for 10 minutes.

[0031] Example 2 1. Prepare vulcanized nitrile: Take 1000 g of nitrile, add 30 g of a 5 wt% potassium hydroxide aqueous solution to adjust the pH value to 9. While stirring, add 35 g, 15 g, and 8 g of 50 wt% zinc oxide slurry, 50 wt% sulfur powder slurry, and 50 wt% accelerator slurry respectively to the nitrile, and continuously stir at a low speed for 24 hours.

[0032] 2. Prepare polyurethane: (1) Under nitrogen protection at 120°C, dehydrate 80 parts by weight of polyol for 5 h. When the water content is below 500 ppm, add 20 parts by weight of isophorone diisocyanate, 6 parts by weight of sodium N-(2-aminoethyl)-2-aminoethanesulfonate, and 3 parts by weight of 1,4-butanediol, stir evenly, then add 0.02 parts by weight of bismuth isooctanoate and 1 part by weight of acetone, and react at 95°C for 3 h to obtain a polyurethane prepolymer; the polyol is a non-crystalline polyether polyol with a number average molecular weight of 6000, a functionality of 6, and a PO / EO ratio of 50%. (2) Cool the prepolymer obtained in step (1) to 55°C, add 30 parts by weight of acetone for dilution, stir evenly, and then add 3 parts by weight of triethylamine and stir for 15 min. (3) Emulsify with 55 parts by weight of deionized water, add 3 parts by weight of ethylenediamine, and after vacuum rotary evaporation to remove the solvent, an aqueous polyurethane emulsion can be obtained.

[0033] 3. Take 95 g of vulcanized nitrile, mix it with 20 g of aqueous polyurethane resin. Take 75 g of the above mixture, stir evenly, add 4 g of deionized water, and then add 5 g of a 2 wt% sodium carboxymethyl cellulose aqueous solution. Add 1 g of white paste and 0.5 g of black paste, stir evenly, mechanically foam to a magnification of 1.2, then stabilize the foam at a low speed for 10 minutes. Finally, adjust the solid content of the latex to 42 wt% with deionized water or a 2 wt% sodium carboxymethyl cellulose aqueous solution, and the construction viscosity is 1800 cp.

[0034] 4. Preheat the hand mold in an oven at 45°C for 30 minutes. After taking it out, put the glove core on the hand mold. First, immerse it with the palm down in a 3wt% calcium nitrate methanol solution, take it out and flash dry for 50 seconds. Then, immerse it with the palm down in the prepared latex, take it out and spin the latex 20 times. Next, slowly immerse the rubber surface in a 10wt% acetic acid methanol solution for 3 seconds, take it out and air dry at room temperature for 30 minutes. Then put it in an oven at 90°C and bake for 40 minutes. After taking it out, wash it with water, and then carry out programmed temperature baking at 90°C for 40 minutes, 105°C for 20 minutes, and 110°C for 10 minutes.

[0035] Example 3 1. Prepare vulcanized nitrile: Take 1000g of nitrile, add 30g of a 5wt% potassium hydroxide aqueous solution to adjust the pH value to 9. While stirring, add 50g, 10g, and 15g of a 50wt% zinc oxide slurry, a 50wt% sulfur powder slurry, and a 50wt% accelerator slurry respectively to the nitrile, and continuously stir at a low speed for 48 hours.

[0036] 2. Prepare polyurethane: (1) Under nitrogen protection at 120°C, dehydrate 80 parts by weight of polyol for 5 h. When the water content is below 500 ppm, add 20 parts by weight of isophorone diisocyanate, 6 parts by weight of sodium ethylenediamine ethylsulfonate, and 3 parts by weight of 1,4-butanediol, stir evenly, then add 0.02 parts by weight of bismuth isooctanoate and 1 part by weight of acetone, and react at 95°C for 3 h to obtain a polyurethane prepolymer; the polyol is an amorphous polyether polyol with a number average molecular weight of 6000, a functionality of 6, and a PO / EO ratio of 50%. (2) Cool the prepolymer obtained in step (1) to 55°C, add 30 parts by weight of acetone for dilution, stir evenly, then add 3 parts by weight of triethylamine and stir for 15 min. (3) Emulsify with 55 parts by weight of deionized water, add 3 parts by weight of ethylenediamine, and after vacuum rotary evaporation to remove the solvent, the aqueous polyurethane emulsion can be obtained.

[0037] 3. Take 450g of vulcanized nitrile, mix it with 50g of aqueous polyurethane resin. Take 320g of the above mixture, stir evenly, then add 30g of deionized water, and then add 40g of a 2wt% sodium carboxymethyl cellulose aqueous solution. Add 8g of white paste and 4g of black paste, stir evenly, mechanically foam to 1.2 times the original volume, then stabilize the foam at a low speed for 10 minutes. Finally, adjust the solid content of the latex to 40wt% with deionized water or a 2wt% sodium carboxymethyl cellulose aqueous solution, and the construction viscosity is 1600cp.

[0038] 4. Preheat the hand mold in an oven at 45°C for 30 minutes. After taking it out, put the glove core on the hand mold. First, immerse it with the palm down in a 2wt% calcium nitrate methanol solution, take it out and flash dry for 50 seconds. Then, immerse it with the palm down in the prepared latex, take it out and spin the latex off 20 times. Next, slowly immerse the rubber surface in a 5wt% acetic acid methanol solution for 2 seconds, take it out and air dry at room temperature for 30 minutes. Then put it in an oven at 90°C and bake for 40 minutes. After taking it out, wash it with water, and then carry out programmed temperature baking: bake at 90°C for 40 minutes, bake at 105°C for 20 minutes, and bake at 110°C for 10 minutes.

[0039] Comparative Example 1 Take 1000g of nitrile, add 30g of an aqueous potassium hydroxide solution with a concentration of 5wt% to adjust the pH value to 9. While stirring, add 35g, 10g, and 8g of 50wt% zinc oxide slurry, 50wt% sulfur powder slurry, and 50wt% accelerator slurry respectively to the nitrile, and continuously stir at low speed for 24 hours.

[0040] Take 500g of vulcanized nitrile, add 22g of an aqueous sodium carboxymethyl cellulose solution with a concentration of 2wt%. Add 2g of white paste and 1g of black paste, stir evenly and mechanically foam to a magnification of 1.2, then stabilize the foam at low speed for 10 minutes. Finally, adjust the solid content of the latex to 38.8wt% with deionized water or an aqueous sodium carboxymethyl cellulose solution with a concentration of 2wt%, and the construction viscosity is 1800cp.

[0041] Preheat the hand mold in an oven at 45°C for 30 minutes. After taking it out, put the glove core on the hand mold. First, immerse it with the palm down in a 2wt% calcium nitrate methanol solution, take it out and flash dry for 50 seconds. Then, immerse it with the palm down in the prepared latex, take it out and spin the latex off 20 times. Next, slowly immerse the rubber surface in a 5wt% acetic acid methanol solution for 2 seconds, take it out and air dry at room temperature for 30 minutes. Then put it in an oven at 90°C and bake for 40 minutes. After taking it out, wash it with water, and then carry out programmed temperature baking: bake at 90°C for 40 minutes, bake at 105°C for 20 minutes, and bake at 110°C for 10 minutes.

[0042] Comparative Example 2 The preparation method of polyurethane is the same as that in Example 1. 1. Take 1000g of nitrile, add 30g of an aqueous potassium hydroxide solution with a concentration of 5wt% to adjust the pH value to 10. While stirring, add 35g, 10g, and 8g of 50wt% zinc oxide slurry, 50wt% sulfur powder slurry, and 50wt% accelerator slurry respectively to the nitrile, and continuously stir at low speed for 24 hours.

[0043] 2. Take 95 g of vulcanized nitrile, mix it with 20 g of waterborne polyurethane resin. Take 75 g of the above mixture, stir it evenly, then add 4 g of deionized water, and then add 5 g of an aqueous solution of sodium carboxymethyl cellulose with a concentration of 2 wt%. Add 1 g of white paste and 0.5 g of black paste, stir evenly, mechanically foam it to 1.2 times the original volume, then stabilize the foam at low speed for 10 minutes. Finally, adjust the latex solid content to 42 wt% with deionized water or a 2 wt% aqueous solution of sodium carboxymethyl cellulose, and the construction viscosity is 1800 cp.

[0044] 3. First, preheat the hand mold in an oven at 45 °C for 30 minutes. After taking it out, put the glove core on the hand mold. First, immerse it palm-down in a 5 wt% acetic acid methanol solution, take it out and flash dry for 50 seconds. Then, immerse it palm-down in the prepared latex, take it out and shake off the latex 20 times. Then, slowly immerse the rubber surface in a 5 wt% acetic acid methanol solution for 3 seconds, take it out and air dry at room temperature for 30 minutes. Put it in an oven at 90 °C and bake for 40 minutes. After taking it out, wash it with water, and then carry out programmed temperature baking: bake at 90 °C for 40 minutes, bake at 105 °C for 20 minutes, and bake at 110 °C for 10 minutes.

[0045] Table 1 Performance comparison of examples and comparative examples The machine wash resistance performance is measured by washing in a washing machine 3 times, 45 minutes each time.

[0046] As can be seen from Table 1, in Examples 1-2, due to the blending of waterborne polyurethane resin in the nitrile emulsion system, the overall hand feeling is significantly softer and more skin-friendly than that of Comparative Example 1. The characteristic of this waterborne polyurethane resin is that it is softer, which can effectively improve the soft and elastic properties of the nitrile emulsion coating, making it comfortable to wear for a long time.

[0047] On the other hand, the penetration performance of this waterborne polyurethane resin is also significantly better than that of the nitrile emulsion. Figure 1 This is the microscope photo of Example 1. Figure 2 This is the microscope photo of Comparative Example 1. From the comparison photos, it can be clearly seen that the colloidal penetration of the blended waterborne polyurethane resin is better. Although the softness of the waterborne polyurethane is not conducive to wear resistance to a certain extent, its excellent penetration performance makes up for the possible decrease in wear resistance caused by softness. At the same time, the penetration will also enhance the bundling of the glove rubber on the glove core yarn, greatly improving the adhesion of the glove rubber on the yarn, and significantly enhancing the water resistance and durability of the labor protection glove rubber.

[0048] Judging from the data, the wear resistance of Example 2 is significantly better than that of Comparative Example 2 because they use different coagulants. Generally, calcium salts are used as coagulants and acetic acid methanol solution is used as a surface treatment agent in production. Another characteristic of this waterborne polyurethane resin is that it coagulates with salts but does not coagulate with acids, which is more conducive to the penetration of the glove rubber during dipping and the shaping after surface treatment.

[0049] In summary, the labor protection gloves prepared from the waterborne polyurethane mixed with nitrile emulsion with strong penetration, high wear resistance and soft hand feel are significantly better than the gloves prepared from nitrile emulsion in terms of hand feel, penetration and wear resistance, and also significantly improve the wearing experience of customers.

[0050] The above embodiments have detailed the structure, features and effects of the present invention. The above are only the preferred embodiments of the present invention. Any changes made according to the concept of the present invention, or equivalent embodiments modified into equivalent changes, still within the scope covered by the specification, shall be within the protection scope of the present invention.

Claims

1. A method for preparing an environmentally friendly waterborne polyurethane modified nitrile latex, characterized in that: The following steps are involved: (1) Preparation of sulfurized butyronitrile; (2) preparing polyurethane; the polyol accounts for 60wt%-85wt% in the polyurethane structure; the functionality of the polyol is 3-6, the PO / EO ratio is 20%-50%, and the number average molecular weight is 2000-6000; (3) Mixing the sulfurized nitrile and the waterborne polyurethane resin in a mass ratio of (80-95):(5-20) to obtain a mixture of the sulfurized nitrile and the waterborne polyurethane resin, adding 4-10 parts by weight of deionized water, 5-10 parts by weight of a thickener, 1-2 parts by weight of a white slurry, and 0.5-1 parts by weight of a black slurry to 75-87 parts by weight of the mixture of the sulfurized nitrile and the waterborne polyurethane resin, and then mechanically foaming to 1.2 times of the original volume, and stabilizing the foam for 5-10 minutes; finally, adding a thickener to make the above mixture reach a construction solid content of 38-42wt% and a viscosity of 1500-1800cp, thereby obtaining an environmentally friendly waterborne polyurethane modified nitrile latex.

2. The preparation method according to claim 1, characterized in that: The method for preparing sulfurized nitrile in step 1 is: adjusting the pH value of the nitrile emulsion to 9-10 with a 5wt% potassium hydroxide solution, adding 50wt% zinc oxide slurry, 50wt% sulfur powder slurry and 50wt% accelerator slurry while stirring, mixing evenly and continuously stirring for 24-48 hours to obtain sulfurized nitrile; the mass ratio of the zinc oxide slurry, the sulfur powder slurry and the accelerator slurry is (30:50): (10-15): (8-15).

3. The preparation method according to claim 1, characterized in that: The thickener in step 3 is 2 wt % of hydroxymethyl cellulose.

4. An environmentally friendly waterborne polyurethane modified nitrile latex prepared by the preparation method as claimed in claim 1.

5. A use of the environmentally friendly waterborne polyurethane modified nitrile latex as claimed in claim 4 in labor protection gloves, characterized in that: The application method is as follows: first preheat the hand mold in a 40-45°C oven for 30 minutes, take it out and put the glove core on the hand mold, first dip the palm downward into the coagulant, take it out and flash dry for 40-60 seconds, then dip the palm downward into the environmentally friendly water-based polyurethane modified nitrile latex, take it out and shake off the latex that cannot adhere to the surface, then dip the rubber surface into the surface treatment agent for 2-3 seconds, take it out and dry it at room temperature for 30 minutes, put it in a 90°C oven and bake it for 40 minutes, take it out and wash it with water, then perform programmed temperature rising baking, and finally obtain the nitrile mixed polyurethane gloves.

6. The use according to claim 5, characterized in that: The coagulant is a 1.5-3wt% calcium nitrate methanol solution; the surface treatment agent is a 5-10wt% acetic acid methanol solution.

7. The use according to claim 5, characterized in that: The programmed temperature rise is baking at 90° C. for 40 minutes, baking at 105° C. for 20 minutes, and baking at 110° C. for 10 minutes.

Citation Information

Cited By

  • Environment-friendly butyronitrile glove and preparation method thereof

    CN121319483A